Pemberlakuan Sistem Satu Orang Satu Suara (One Man One Vote) Dalam Pemilihan Pengurus Dan Pengawas Perhimpunan Pemilik Dan Penghuni Satuan Rumah Susun - Stevenson, Jerry; F. R., Mella Ismelina (Jurnal Hukum & Pembangunan, 2020)
Article 19 Regulation of the Minister of Public Works and Public Housing Number 23 / PRT / M / 2018 concerning the Association of Owners and Occupants of Apartment Units enforces the election of Management and Supervisors of the Association of Apartment Owners and Residents of Apartment Units only by the most votes (without prioritizing deliberation) and with one person one vote system, and with conditions that only the Owner can fulfill. Thus it can be agreed that the election of Management and Supervisors of the Association of Owners and Occupants of Apartment Units is a voting right. The purpose of writing this thesis is to see or reveal the background or considerations of the application of the one man one vote system in the selection of the Management and Supervisor of the Association of Owners and Managers of Apartment Units, and to analyze the extent to which these provisions are contrary to the principle of voting rights in the field of Flat Law.